Biomassa e carbono no estrato arbóreo em área de restauração e em floresta semidecidual - Silva, Helane França (2014)
This study was conducted with the objective of estimating the biomass and carbon stocks in the tree extract of a restoration area with 21 years of age, and in a remnant of semideciduous forest, both located around Camargos’ dam in the municipality of Itutinga, southern Minas Gerais, Brazil. The study areas presented permanent 20 m x 20 m plots, in which we measured diameter and height, and identified all trees with CBH ≥ 15 cm. The basic wood density (BWD) and carbon content were determined for the species of highest ecological importance in each study area. The biomass stock was indirectly estimated using an allometric equation. The carbon stock was determined by multiplying the dry biomass and the carbon content obtained in laboratory. In the restoration area, the species with the lowest and highest carbon content were Lafoensia vandelliana (43.70%) and Anadenanthera peregrina (46.60%), respectively. As for the BWD, the species presenting the lowest and highest values were Cecropia pachystachya (0.31 g cm-3) and Anadenanthera peregrina (0.72 g cm-3), respectively. In the forest remnant, the species with the lowest and highest carbon content were Casearia decandra (41.85%) and Nectandra oppositifolia (46.57%), respectively. For BWD, the species presenting the lowest and highest values were Nectandra lanceolata (0.38 g cm-3) and Machaerium villosum (0.77 g cm-3), respectively. The biomass and carbon stocks of the restoration area were of 109.40 t ha-1 and 49.73 t ha-1, respectively, with a periodic annual increment (PAI) of 3.72 t ha-1 ano-1 (2010 - 2013). In the forest remnant, the biomass stock was of 126.92 t ha-1, which corresponded to 55.91 t ha-1 of carbon and a PAI of 0.61 t ha-1 ano-1. The information generated by this study may provide support for natural forest conservation programs and degraded landscape restoration initiatives which aim to promote an in site increase of carbon stock and forest carbon credit trading.